2005
DOI: 10.1111/j.0022-1112.2005.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

The silvering process of Anguilla anguilla: a new classification from the yellow resident to the silver migrating stage

Abstract: The identification of five stages for female and two stages for male eels Anguilla anguilla using multivariate analysis was carried out on a large sample of individuals collected at six different locations in France. Stages corresponded to a growth phase (stages I and II), a pre-migrant phase (III) and two migrating phases (IV and V). It is likely that an important period of growth triggered silvering through the production of growth hormone (GH) in stage III eels. In migrating eels gonad development, gonadotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
385
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(415 citation statements)
references
References 56 publications
23
385
2
5
Order By: Relevance
“…However, the average length or weight of tagged eels did not differ significantly between the capture sites within each year (2-way ANOVA, year × site interaction, F 1, 95 = 3.7 for length and F 1, 95 = 1.01 for weight, p > 0.05 in both cases, Table S1 in the Supplement). The maturity of each eel was judged by 2 indices, the ratio between eye area and body length (BL) (Pankhurst 1982) and the ratio between the length of the pectoral fin and BL (Durif et al 2005). According to those indices, all eels were in the silver eel stage.…”
Section: Eel Tagging and Releasementioning
confidence: 99%
“…However, the average length or weight of tagged eels did not differ significantly between the capture sites within each year (2-way ANOVA, year × site interaction, F 1, 95 = 3.7 for length and F 1, 95 = 1.01 for weight, p > 0.05 in both cases, Table S1 in the Supplement). The maturity of each eel was judged by 2 indices, the ratio between eye area and body length (BL) (Pankhurst 1982) and the ratio between the length of the pectoral fin and BL (Durif et al 2005). According to those indices, all eels were in the silver eel stage.…”
Section: Eel Tagging and Releasementioning
confidence: 99%
“…Although the ocular hypertrophy values (OI > 6.5) should be considered as a criterion for silver eel determination (Acou et al, 2005) it was not calculated in the field for logistic reasons. However, Durif et al (2005) showed that the increase in the ocular diameter appears before the pigmentation change, therefore we considered it valid to use only the two criteria. Silver eels were marked with acrylic paint ("Van Gogh" permanent green light 618) and ink ("Magic Color" process magenta MC 620).…”
Section: > Colour-marking Experimentsmentioning
confidence: 99%
“…Later in the season, some eels build up higher lipid contents and start to migrate to sea to begin their journey to the Sargasso Sea [11]. Although those 'silver eels' can be distinguished by their grey colour, in contrast with the regular 'yellow eel', mistakes in this identification can be made [12]. Farmed eel were purchased from 11 Dutch eel farmers.…”
Section: Eel Studymentioning
confidence: 99%